The night before christmas - Moore, Clement Clarke, 1779-1863; Engelbreit, Mary ([New York] : HarperCollins Publishers, 2002)
A newly illustrated version of the well-known poem about an important Christmas visitor.
Keywords: Santa Claus -- Juvenile poetry; Christmas poetry; Children's poetry, American; Santa Claus -- Poetry; Christmas -- Poetry; American poetry; Narrative poetry